Effects of mycorrhiza on growth and essential oil production in selected aromatic plants - Tarraf, Waed; Ruta, Claudia; De Cillis, Francesca; Tagarelli, Anna; Tedone, Luigi; De Mastro, Giuseppe (Italian Journal of Agronomy, 2015)
Arbuscular mycorrhizal (AM) symbiosis is widely investigated in aromatic herbs. Several studies have shown different effects on secondary metabolites, biomass production, as well as oil quantitative and qualitative aspects. The seeking to increase the yield of plants and their oils is an interesting topic in the world of medicinal and aromatic plant production. In tune with that, this study evaluated the effectiveness of two mycorrhiza fungi, Funneliformis mosseae (syn. Glomus mosseae) and Septoglomus viscosum (syn. Glomus viscosum), on three species from Lamiaceae family: Salvia officinalis L., Origanum vulgare L., and Thymus vulgaris L. besides untreated control. It was found that the effect of symbiosis on growth was more favourable with S. viscosum than other AM fungus. The S. viscosum inoculation raised the yield of essential oil in oregano. Analysis of gas chromatography/mass spectrometry showed that manool obtained the highest abundance in leaf essential oil of inoculated sage; thymol was the major component whatever the treatment in thyme and lower relative content of carvacrol was reported with arbuscular mycorrhizal fungi inoculation in oregano. The results suggest the mycorrhizal inoculation as a promising technology in sustainable agricultural system to improve the plant productivity performance. Specific inocula are strategic to enhance the chemical profile of essential oils.